问题 解答题
已知
a+b-c
c
=
a-b+c
b
=
-a+b+c
a
,求
(a+b)(a+c)(b+c)
abc
的值.
答案

解法1:(1)若a+b+c≠0,由等比定理有

a+b-c
c
=
a-b+c
b
=
-a+b+c
a

=

a+b-c+a-b+c-a+b+c
a+b+c

=1,

所以a+b-c=c,a-b+c=b,-a+b+c=a,

于是有

(a+b)(a+c)(b+c)
abc
=
2c•2b•2a
abc
=8.

(2)若a+b+c=0,则a+b=-c,b+c=-a,c+a=-b,

于是有

(a+b)(a+c)(b+c)
abc
=
(-c)(-a)(-b)
abc
=-1.

解法2:若

a+b-c
c
=
a-b+c
b
=
-a+b+c
a
=k,

则a+b=(k+1)c,①

a+c=(k+1)b,②

b+c=(k+1)a.③

①+②+③有2(a+b+c)=(k+1)(a+b+c),

所以(a+b+c)(k-1)=0,

故有k=1或a+b+c=0.

当k=1时,

(a+b)(a+c)(b+c)
abc
=
2c•2b•2a
abc
=8.

当a+b+c=0时,

(a+b)(a+c)(b+c)
abc
=
(-c)(-a)(-b)
abc
=-1.

选择题
单项选择题